The Impact of Poverty on the Livelihoods of Internally Displaced Persons Galkio Puntland Somalia - Abdi, Abdiladif Mursal (International Journal of Scientific Research and Management (IJSRM), 2025)
Poverty remains a critical global issue, disproportionately affecting vulnerable populations, including internally displaced persons (IDPs). This study focuses on the impact of poverty on the livelihoods of IDPs in Galkio, Puntland, Somalia, where displacement due to conflict, climate change, and economic instability has created severe socio-economic challenges. These include high unemployment, lack of access to education and healthcare, food insecurity, and inadequate shelter.The study employs a mixed-methods approach to examine the socio-economic conditions of IDPs, their coping mechanisms, and the effectiveness of humanitarian and governmental interventions. The findings show that IDPs struggle to secure sustainable livelihoods, often depending on short-term aid instead of long-term economic opportunities. Vulnerable groups, such as women, children, and persons with disabilities, face additional challenges, including gender-based violence, marginalization, and limited access to essential services.Despite efforts by humanitarian organizations, current interventions often fail to address the root causes of poverty and displacement effectively. The study stresses the urgent need for policies that foster long-term economic empowerment, skills development, and income-generating opportunities for IDPs. By addressing poverty in displacement contexts, these policies could promote self-sufficiency, social integration, and long-term resilience for IDPs. Ultimately, the research aims to contribute to ongoing efforts to improve the living conditions and livelihoods of IDPs in Somalia and offer recommendations for more sustainable interventions.